Overexpression of the MRI Reporter Genes Ferritin and Transferrin Receptor Affect Iron Homeostasis and Produce Limited Contrast in Mesenchymal Stem Cells - Pereira, Sofia M. (Int J Mol Sci, 2015)
Imaging technologies that allow the non-invasive monitoring of stem cells in vivo play a vital role in cell-based regenerative therapies. Recently, much interest has been generated in reporter genes that enable simultaneous monitoring of the anatomical location and viability of cells using magnetic resonance imaging (MRI). Here, we investigate the efficacy of ferritin heavy chain-1 (Fth1) and transferrin receptor-1 (TfR1) as reporters for tracking mesenchymal stem cells. The overexpression of TfR1 was well tolerated by the cells but Fth1 was found to affect the cell’s iron homeostasis, leading to phenotypic changes in the absence of iron supplementation and an upregulation in transcript and protein levels of the cell’s endogenous transferrin receptor. Neither the sole overexpression of Fth1 nor TfR1 resulted in significant increases in intracellular iron content, although significant differences were seen when the two reporter genes were used in combination, in the presence of high concentrations of iron. The supplementation of the culture medium with iron sources was a more efficient means to obtain contrast than the use of reporter genes, where high levels of intracellular iron were reflected in transverse (T(2)) relaxation. The feasibility of imaging iron-supplemented cells by MRI is shown using a 3R-compliant chick embryo model.